A Study on Financial Performance of Bajaj Finserv Limited - JOGHEE, MEHTA VANI; DHARANI, S.; RITHIKA, S.; DARSHINI, VISHNU (The journal of contemporary issues in business and government, 2021)
Financial analysis is referred to as financial statement analysis or accounting analysis. It refers to an assessment of the viability, stability and profitability of a business, sub-business or project. The main idea behind this study is to analyze the financial operating position of the company. This research is done with help of secondary data which is gathered from the annual report of the company. The financial performance can be measured by using various financial tools such as profitability ratio, solvency ratio, CAGR, etc. Based on the analysis, findings have been arrived at that the company has got enough funds to meet its debts & liabilities and the income statement of the company shows sales of the company increased every year at good rate and profit also increased every year.